Text processing with Javascript: regular expressions, tools, and techniques for optimal performance - Kelhini, Faraz K (The Pragmatic Bookshelf, 2023)
You might think of regular expressions as the holy grail of text processing, but are you sure you aren't just shoehorning them in where standard built-in solutions already exist and would work better? JavaScript itself provides programmers with excellent methods for text manipulation, and knowing how and when to use them will help you write more efficient and performant code. From extracting data from APIs to calculating word counts and everything in between, discover how to pick the right tool for the job and make the absolute most of it every single time.Whether you're a beginner or an advanced programmer, this up-to-date guide will save you a ton of time when dealing with text. With Text Processing with JavaScript, you'll find a collection of tiny programs, each demonstrating a string manipulation approach in JavaScript. You'll also focus squarely on the practical aspects of text processing with JavaScript - that is, what each technique is designed to accomplish and how to use it in your program.Discover how to extract data from APIs and web pages, apply spelling corrections, convert and format currencies, and remove HTML tags from text. Learn to intersect tables, copy text to the clipboard, extract lists from text, and highlight sentences that contain a specific word. Find duplicate words and fix them automatically, modify a copy of an existing regex literal, match the beginning or end of a string, and remove all comments from JavaScript and HTML files with ease. Match non-ASCII words, calculate the word count of an article in any language, and more.Become a JavaScript expert and master chef of text processing with this collection of hands-on and production-ready recipes.